"Selametan Tolak Bala" as Coping Strategy During the Covid-19 Pandemic - Septian, Ade; Yunanto, Taufik Akbar Rizqi (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
Selametan tolak bala is a ritual that Javanese people usually do during the pagebluk period. During the current Covid-19 pandemic, some people still carry out this ritual. This study seeks to examine from a psychological point of view why the ritual is still carried amid restrictions on community activities. This research was conducted by literature review method using sources from books, previous research, articles from mass media and website pages, aiming to collect theories and pieces of information relevant to the topics studied in this research. The results of this research are selametan tolak bala could be a form of problem-focused coping if the practitioners believed that this ritual could stop the outbreak. It could be a form of emotional-focused coping if the practitioners believed that this ritual is done to eliminate the anxiety. As Javanese local wisdom, whatever the meaning coping strategies, selametan tolak bala could be one of the efforts in dealing with the Covid-19 pandemic, especially in reducing anxiety levels. Therefore it had to be done by enforcing strict health protocols to avoid the possibility of increasing positive cases of Covid-19 after the ritual implementation, which thwarts the ritual’s purpose.